Assessment of avenin and aflatoxin B1 in Avena sativa - Divyashree J Seshagiri, Dr.GhadevaruSarathchandra (International Journal of Advanced Science and Technology, 2020)
Oats is one of the staple food consumed by all classes of people.Due to its nutritive value, oats are preferred as diet food.Owing to its triggering property for celiac disease, including oats in a gluten-free diet has become controversial. The main reason for this intolerance is the avenin, a prolamin similar to gluten, which has a high proline (amino acid) content. The extraction process of avenin from oat samples is done by 50%(v/v) Isopropanol. The isolated protein is analyzed under HPTLC (High-Performance Thin Layer Chromatography). The quantification of avenin in each variety and its properties are studied.The prolamin content (avenin) in the oat varieties is approximately 4-10% of its total protein as per the international studies. Thus the concentration of avenin in each sample can be analyzed and compared. The additional qualitative parameters such as moisture content, water-activity and microbial growth are also analyzed